The Impact of The Green Marketing Mix Strategy on Consumer Purchasing Decisions at KFC Fast Food Restaurants - Abdullah, Muhamad Al Faruq; Achmad Tarmizi (Siber Journal of Advanced Multidisciplinary, 2024)
This study focuses on how implementing a green marketing mix strategy can influence consumer purchasing intentions. The green marketing mix strategy involves using environmentally friendly concepts in every element of the marketing mix, which includes product, price, place, and promotion. Data were analyzed using the Structural Positive and Equation Model (SEM) Partial Least Square (smartPLS 3.0) application to identify the implementation of the green marketing mix strategy and analyze the influence of the green marketing mix strategy on consumer purchasing decisions. This research uses a quantitative approach by collecting data through questionnaires distributed to KFC Tanjung Duren consumers. Based on the hypothesis testing in this research, the results show that Green Place has a positive relationship but does not have a significant effect on Purchasing Decisions, Green Price has a positive and significant relationship with Purchasing Decisions, Green Product has a negative and significant relationship with Purchasing Decisions, Green Promotion has a positive relationship and has a significant effect on purchasing decisions. Overall, the Green Marketing Mix analysis shows that environmentally friendly promotions and prices play an important role in consumer purchasing decisions.